Budidaya Tanaman Sayuran Menggunakan Sistem Pendukung Keputusan Dengan Metode Profile Matching - Dhella Amelia; Revi Gusriva (Universitas Budi Darma, 2022)
Cultivating vegetable plants is very important for farmers. In the cultivation of vegetable plants, there are problems that are often faced by farmers, one of which is the lack of information about natural conditions and limited knowledge of farmers. so it is necessary to have an auxiliary media in the form of a system that can provide solution information at any time. Selection of plants that are not suitable will get unsatisfactory results. Farmers must know that what needs to be considered in cultivating vegetable crops is compatibility with natural conditions. This research builds a web-based decision support system software regarding vegetable cultivation that meets the criteria using the profile matching method as a tool to facilitate the decision-making process with several comparison criteria, namely: temperature, sunlight, rainfall and humidity, altitude, harvest time, marketability, susceptibility to disease, and level of care. This application is made web-based using PHP as the programming language and MySQL as the data storage. The purpose of this application is to provide effective and efficient information to farmers in making decisions and alternatives that are in accordance with the natural conditions of the area. The result of making this system is that farmers make the right decisions when cultivating vegetables based on the criteria.